New experimental set up for ACB tomography - Matos, R. V.R. [UNESP] (2015)
New tomographic methods for the formation of free ionizing radiation has attracted great interest in the last decades, including the biosusceptometry AC tomography has important characteristic that can be exploited for the formation of these images, as well as a relevant versatility, sensitivity, low cost and is already being used for imaging for studies in physiology and pharmacology. As the main objective of this work, we characterize a new ACB tomography system. Some factors such as the sensitivity and resolution of systems have a direct relationship with an improvement in these images, so the search for new instrumentation that entail this sort of improvement are important to this area of research.